Analisis Penerapan Manajemen Risiko dalam Program Pendidikan untuk Peningkatan Mutu Sekolah - Dearna Esza; Irsyad, Irsyad; Merika Setiawati (CV. ITTC INDONESIA, 2025)
This study aims to analyze the implementation of risk management in educational programs as a strategy for improving school quality. A qualitative descriptive approach was used through a literature review and analysis of risk management practices in educational institutions. The results indicate that the implementation of risk management plays a crucial role in ensuring the success of educational programs. Schools that systematically implement risk identification, analysis, and mitigation processes are able to prevent program failure, optimize resources, and increase public trust in school quality. Effective mitigation strategies include teacher training, funding diversification, and ongoing evaluation of school activities. Thus, risk management is not only a control tool but also a strategic instrument for achieving sustainable educational quality.